Gesondheidsopvoedkundige Benadering Tot Vektorbeheer - E.K. Hartwig (AOSIS, 1979)
Vector control in South Africa is governed by specific factors which must be taken into account in educational programs. Our basic aim is prevention. The community is directly concerned and must be educated in vector control and preventive measures. Present day border conditions and communication problems complicate matters. The various population groups necessitate different approaches. Understanding and goodwill are essential for success in vector control.